1988
DOI: 10.1200/jco.1988.6.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy of osteosarcoma: results of a randomized cooperative trial (COSS-82) with salvage chemotherapy based on histological tumor response.

Abstract: Following observation of the predictive value of the histologic extent of tumor cell destruction after preoperative chemotherapy for metastasis-free survival (MFS) in osteosarcoma, a randomized study was undertaken with the aim of (1) sparing some patients the unpleasant side effects of highly toxic drugs like doxorubicin (DOX) and cisplatin (CPDD) by administering these drugs postoperatively only after poor response with a milder preoperative regimen, and (2) improving the prognosis of patients responding poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
2
17

Year Published

1991
1991
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(178 citation statements)
references
References 8 publications
1
158
2
17
Order By: Relevance
“…15 In general, however, the effect of chemotherapy is only temporary, and preoperative chemotherapy should be followed by intensive local treatment. In recent years, not only chemotherapy [7][8][9][10]17 and imaging techniques 28 but also surgical techniques 20,25,29 -31 have been developed in spinal sarcoma surgery. Kawahara et al 14 reported reconstruction after en bloc resection of the affected vertebra by osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…15 In general, however, the effect of chemotherapy is only temporary, and preoperative chemotherapy should be followed by intensive local treatment. In recent years, not only chemotherapy [7][8][9][10]17 and imaging techniques 28 but also surgical techniques 20,25,29 -31 have been developed in spinal sarcoma surgery. Kawahara et al 14 reported reconstruction after en bloc resection of the affected vertebra by osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency towards radical tumor surgical removal with amputation [11][12][13] has given way to programs with extremity preservation by combining surgery and neoadjuvant and adjuvant radiation therapy and chemotherapy without compromising the results in disease-free survival [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the COSS protocols COSS 80, COSS 82, COSS 86, COSS 86C, and COSS 91 [7][8][9][10] , patients were designated to receive high-dose methotrexate with leucovorin 17,18 In COSS 80 through COSS 96, both preoperative and postoperative chemotherapy were scheduled. [7][8][9][10]17 All studies were approved by the local ethics committee and/or the protocol review committee of the German Cancer Society or the German Ministry for Science and Technology.…”
Section: Treatment Planmentioning
confidence: 99%
“…[7][8][9][10]17 All studies were approved by the local ethics committee and/or the protocol review committee of the German Cancer Society or the German Ministry for Science and Technology. Before the initiation of treatment, informed consent was obtained from all patients or their legal guardians.…”
Section: Treatment Planmentioning
confidence: 99%